Neonatal hypoxic ischemic encephalopathy-related biomarkers in serum and cerebrospinal fluid - Lv, Hongyan; Wang, Qiuli; Wu, Sujing; Yang, Lihong; Ren, Pengshun; Yang, Yihui; Gao, Jinsheng; Li, Lianxiang (Clinica chimica acta, 2015)
Neonatal hypoxic ischemic encephalopathy (HIE) is a common disease caused by perinatal asphyxia, a major cause of neonatal death, neurological behavior, and long-term disability. Currently, the diagnosis and prognosis of neonatal HIE are based on nervous system clinical manifestations, imaging and electrophysiological examination. These take time and late diagnosis allows brain injury to occur in newborns, so that infants of many brain injury missed the best treatment time, left with varying degrees of neurological sequelae. The use of biomarkers to monitor brain injury and evaluate neuroprotective effects might allow the early intervention and treatment of neonatal HIE to reduce mortality rates. This study reviewed the mechanism of neonatal hypoxic ischemic encephalopathy in relation to numerous brain-related biomarkers including NSE, S-100β, GFAP, UCH-L1, Tau protein, miRNA, LDH, and CK-BB. In early diagnosis of neonatal HIE, S-100β and activin A seems to be better biomarkers. Biomarkers with the greatest potential to predict long-term neurologic handicap of neonates with HIE are GFAP and UCH-L1 and when combined with other markers or brain imaging can increase the detection rate of HIE. Tau protein is a unique biological component of nervous tissues, and might have value for neonatal HIE diagnosis. Combination of more than two biological markers should be a future research direction. •Biomarker application in neonatal hypoxic ischemic encephalopathy is introduced.•S-100β and activin A are good markers for early diagnosis of neonatal HIE.•GFAP and UCH-L1 are promising biomarkers to predict the long-term neurologic handicap.•Optimized combination of biomarkers is proposed to enhance neonatal HIE diagnosis.